Study on influencing factors of slope stability and evolution law of safety factor in coal measure strata - Li, Hongru; Yang, Min (Frontiers in Earth Science, 2023)
Aiming at the influence factors and their action regulation of the slope stability in the coal measure strata of Beijing–Hong Kong & Macao Expressway, the influence characteristics of injection dip angle of rock stratum, thickness and strength parameters of the soft interlayer, slope height and size of slope angle on the slope safety factor are systematically studied by using the limit equilibrium method theory. The influence of slope height, thickness of weak interlayer and shear strength parameters on the stability of slope in coal measure strata with different dip angles is that the safety factor decreases first and then increases with the increase of strata dip angle. The minimum safety factor of slope under the action of each factor is near the strata dip angle of 30°, which indicates that the stability of slope in coal measure strata is poor when the dip angle of rock stratum is about 30°. With the increase of slope angle, the minimum safety factor decreases. However, when the slope angle is less than 40°, the slope is in a stable state and the dip angle of the strata do not affect the stability of the slope. Slopes with different slope angles have the minimum safety factor that is not affected by slope height. The difference between analytical solution and numerical solution is analyzed. The research provides a theoretical basis for the treatment of slopes in coal measure strata and has certain practical significance.